Leashes, Litterboxes, and Lifelines: Exploring Volunteer-Based Pet Care Assistance Programs for Older Adults - McLennan, Kate; Rock, Melanie J.; Mattos, Emma; Toohey, Ann M. (Frontiers in Psychology, 2022)
At the convergence of population aging and pet-ownership, community stakeholders are well-positioned to support older adults’ relationships with companion animals through age-related transitions in health and living arrangements. In this study’s setting, a volunteer-based pet care assistance program launched in 2017 to provide practical assistance with pet care for socially disadvantaged, community-dwelling older adults. This case study explored the impacts and feasibility of this and similar programs via (i) an Internet-based environmental scan to compare similar programs and (ii) qualitative interviews with a sampling of diverse community stakeholders (n=9). A small number of comparable international programs (n=16) were found. Among these, programs were delivered using a range of funding models; fewer than half involved collaborations across human social services and animal welfare sectors; and none addressed all dimensions of support offered by our local program. Analysis of qualitative interviews highlighted five major themes confirming the value of the volunteer-based approach and the importance of cross-sectoral collaborations in addressing older adults’ under-recognized pet care-related needs. Taken together, the findings confirmed the effectiveness of our local program model. Collaborative, cross-sectoral programs that target both human and companion animal well-being hold promise to reduce barriers to pet ownership that many disadvantaged older adults face. This unique approach leverages the health-promoting potential of human-animal relationships in ways that enhance quality of life for individuals, animal welfare, and age-friendliness of communities.